2015
DOI: 10.1371/journal.pntd.0004011
|View full text |Cite
|
Sign up to set email alerts
|

Use of Recombinant Virus Replicon Particles for Vaccination against Mycobacterium ulcerans Disease

Abstract: Buruli ulcer, caused by infection with Mycobacterium ulcerans, is a necrotizing disease of the skin and subcutaneous tissue, which is most prevalent in rural regions of West African countries. The majority of clinical presentations seen in patients are ulcers on limbs that can be treated by eight weeks of antibiotic therapy. Nevertheless, scarring and permanent disabilities occur frequently and Buruli ulcer still causes high morbidity. A vaccine against the disease is so far not available but would be of great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…Moreover, the healing tissue is not sterilized because the viable bacterial load is still high and stable, illustrating the absence of an efficient specific immune response against M. ulcerans. In this context, our results are not in favor of vaccine strategies targeting directly mycobacterial components, as already suggested (12,40,41). Surprisingly, histological approaches showed that the bacilli present in healed tissues are not surrounded by a granuloma-like structure, unlike in the context of latent tuberculosis (42,43).…”
Section: Major Data Model Descriptionsupporting
confidence: 52%
See 1 more Smart Citation
“…Moreover, the healing tissue is not sterilized because the viable bacterial load is still high and stable, illustrating the absence of an efficient specific immune response against M. ulcerans. In this context, our results are not in favor of vaccine strategies targeting directly mycobacterial components, as already suggested (12,40,41). Surprisingly, histological approaches showed that the bacilli present in healed tissues are not surrounded by a granuloma-like structure, unlike in the context of latent tuberculosis (42,43).…”
Section: Major Data Model Descriptionsupporting
confidence: 52%
“…Usually, all preclinical studies of M. ulcerans infection are performed in a mouse model, using either BALB/c or C57BL/6 mouse strains, and they study host colonization or evaluate efficacy of treatments or vaccines (7,(10)(11)(12)(13)(14). As a matter of fact, in both strains, s.c. inoculation with M. ulcerans invariably leads to ulceration after several weeks, with lesions evolving toward tissue necrosis and death of the animals.…”
mentioning
confidence: 99%
“…As repeated passage by in vitro culture prompts some of the M. ulcerans strains to lose their virulence plasmid [47,48], some laboratories opted to passage their strains trough mouse foot pads in order to preserve their virulence [49][50][51]. Alternatively, low passage primary isolates have been used for productive infection of mice [52].…”
Section: Mycobacterial Strains Used For Experimental Infectionmentioning
confidence: 99%
“…S1013 was originally isolated in 2010 from a swab taken from the undermined edges of the ulcerative lesion of a Cameroonian BU patient [57]. Its passage number has been kept to an absolute minimum in order to preserve its virulence for studies in the mouse footpad model and the pig model of BU [40,45,52,[58][59][60].…”
Section: Mycobacterial Strains Used For Experimental Infectionmentioning
confidence: 99%
“…However, this study only evaluated protection for days, and thus it remains to be investigated whether protection is long-lasting. Moreover, it is unclear if protective immunogens could have been removed during the dewaxing process, in spite of a general lack of protection detected in immunization interventions employing surface proteins, such as the 18 kDa shsp and the 27 kDa laminar binding protein [32,160,161]. Still, these results add to others confirming the extreme hydrophobicity of the M. ulcerans cell wall, which cumulatively with mycolactone represents a virulence factor and aids in shielding the pathogen from immune surveillance mechanisms, consequently adding another layer of complexity to the development of preventive strategies [162].…”
Section: (Un)successful Preventive Approachesmentioning
confidence: 99%